The Coast As A Vernacular Region - Mann, Jennifer M. (East Carolina University, 2010)
The study of regions and regional identity is one of the cornerstones of the field of geography. Historically within regionally-based research, there has been interest in vernacular regions and the use of business names as a data source for mapping patterns in regional identity. However, few studies of regional identity and names have taken full advantage of digital methods and the use of powerful online databases and GIS/mapping software. ReferenceUSA, an electronic database was used to collect all business names in the United States that contain the term coast(al). Once data were collected and cleaned, two distinctive avenues of analysis were conducted.   The first was a quantitative mapping of coast(al) business name patterns, finding that even inland establishments identify themselves with the coast. Several maps were produced to visualize the distribution and frequency of coast(al) named businesses and to better understand the spatial patterns of people's identification with the coast as a vernacular region. The second avenue is more of a qualitative image analysis of place naming and branding. Analysis has been done to examine how the physical environment is incorporated into a people's sense of place and why the coast is such a popular and powerful symbol.
Keywords: Geography; Regional studies; Business names--United States; Onomastics--United States; Regionalism--United States; Coasts--United States